Towards a strategy for adapting traditional knowledge at ecosystem: A close look at mezcaleros producers in Mexico - Israel Contreras-Medina, David; Sánchez Osorio, Ever; de Lourdes Flores López, María; Pardo Nuñez, Joaliné; Vázquez Elorza, Ariel (Kasetsart Journal of Social Sciences, 2020)
Population growth, economic crisis and climate change have altered the ecosystem sustainability forcing us to adopt different pathways of interaction. This has affected not only the relationship between man and environment, but also the interaction between society and economic structure, triggering reduced incomes, migration and the abandonment of traditional knowledge able to transform natural resources into food or beverage. Being in line with the objective to achieve sustainable ecosystem, the goal of this study is constructing strategies that contribute to adapting mezcaleros’ traditional knowledge at ecosystem, examining the problems, priorities, strategies and proposals to be undertaken by mezcaleros from Mexico. Using the Hybrid Delphi methodology, in face-to-face and non-face-to-face stage, including six mezcaleros leaders and a research group, the results demonstrated that access to financial institutions and government programs, such as the external activities that must be implemented besides business designing model and plan as priorities in face-to face stage. For the non-face-to-face stage, the priority is to evaluate their organizational capacity, provide detailed organizational tracking, achieving equitable government support and to design a scientific and robust business model. These proposals focus on facilitating adaptation of traditional knowledge at ecosystem without transgressing purity and privacy of the values, customs and local traditions of mezcal communities.